Study on the Effect of Different Factors over the Explosion Range for New Alternative Refrigerants HFC-32 - Wang Yongzhen; Jin Jing; Xiong Zhibo; Meng Lei; Guo Mingshan (Zhileng xuebao)
The influences of temperature, relative humidity and fire-retardant on the explosion range of new alternative refrigerants HFC-32 were investigated through an experiment bed for the explosion range of flammable gases. The results indicated that the enhancement of temperature can improve the upper explosion range of HFC-32 and decrease its lower explosion range, then enlarges the explosion range of HFC-32 under the temperature of﹣5~55 ℃. The improvement of relative humidity makes the lower explosion range of HFC-32 slightly increase, and the upper explosion range slightly decrease at the relative humidity range of less than 60% for HFC-32. When the relative humidity increases from 60% to 87%, the upper explosion range of HFC-32 decreases rapidly to make the explosive range of HFC-32 disappear. The addition of CF3I or HFC-134a fire-retardant can lead the explosion range of HFC-32 to reduce, and the effect of CF3I on the inflaming retarding of HFC-32 is superior to HFC-134a. When the volume ratio of CF3I/HFC-32 increases from 0 to 1 or HFC-134a/HFC-32 increases from 0 to 10, their explosion ranges disappear. This provides an important theoretical basis for inhibiting the combustion of HFC-32.